Parental preferences regarding medium of instruction in primary schools in the Nongoma district of Kwazulu-Natal - Mhlanga, Samkelisiwe Isabel (Rhodes University, Faculty of Education, Department of Education, 1995)
This thesis looks at what choice of medium of instruction (MOl) parents in a rural village in KwaZulu would make if they had the opportunity to choose. The background to this choice goes back to 1979, when Education and Training Act No. 90 established the mother tongue as MOl from Sub A to Std 2 in Department of Education and Training (DET) primary schools, followed by a sudden transition to English medium of instruction - (EMl) in Std 3. Though by 1990 98% of the schools had opted for EMI, conditions were not favourable for a sudden transition and the policy led to high drop-out rates. The problems encountered by teachers and learners were researched and documented by Macdonald in the Threshold Project Reports (1990). Although the Minister initially ignored the Project's findings, in May 1991 he admitted that his department's language policy was leading to serious educational disadvantages. The explosive situation that culminated in the 1976 school uprisings led to the amendment of the Act. There was concern among people involved in educational language policy that parents had not been given sufficient information to make informed educational choices. They feared that many parents would, largely out of ignorance, opt for straight-for-English, when in fact the conditions in the schools were not conducive to the success of that choice option. The widespread assumption about the parents choosing straight-for-English was based on anecdotal evidence. I decided to investigate this matter in the Nongoma area. My findings pointed to very healthy attitudes towards the mother tongue and there was even a measure of understanding of the place of mother tongue instruction in the beginner classes. But even though the respondents wanted their language to be respected, they also wanted their children to acquire a good education in English, so as to be eligible for jobs in an economy that emphasises the importance of English.
Keywords: Native language and education -- South Africa; Language and education -- South Africa; Education -- Parent participation -- South Africa; Language policy -- South Africa